Effect of uncertainty on U.S. stock returns and volatility: evidence from over eighty years of high-frequency data. Issue 16 (19th September 2020) - Gupta, Rangan; Marfatia, Hardik A.; Olson, Eric
ABSTRACT: We explore the asymmetric high-frequency daily response of U.S. equities to financial uncertainty over the 1936–2016 period. We find positive growth of uncertainty reduces stock returns and increases volatility, while, a negative growth of uncertainty primarily reduces variance. More importantly, the impact of uncertainty on volatility is found to be asymmetric. We also model rolling window estimation and find significant time variation in the impact of uncertainty, though the direction largely confirms with the static case. Our study provides new evidence that the response of U.S. equities to uncertainty is intuitively consistent even in the historical and high-frequency context.